The utilization of cold storage through solar PV mini-grids to reduce spoilage in fisheries in Tanzania - Carlsson, Ofelia; Johansson, Madeleine (My University, 2022)
The lack of electricity is a major problem in Sub-Saharan Africa, and a majority of the population live in rural areas where it might be difficult to extend the main grid. Mini-grids are a possible solution, and new mini-grids are continuously built to supply villages with electricity. The access of electricity might in turn be a part of a solution to another major problem, spoilage of fish due to the lack of cold storage. This thesis intents to add to the information of how electricity from a solar PV mini-grid can decrease the spoilage of fish. It also aims to investigate the economical possibility to implement a communal cold storage unit connected to a solar PV mini-grid and what technical requirements it puts on the operation of the mini-grid. The information required were gathered through a literature study and by performing a field study in Tanzania. The thesis is based on a case on the island Ukara in Lake Victoria. The data is used in a techno-economic analysis that simulates a walk-in cold storage room connected to a solar PV mini-grid on the island Ukara in Tanzania. The thesis also consists of a qualitative analysis, where a causal loop diagram illustrates the interlinkages between the variables in the system to identify the effects of electricity on the spoilage of fish. The findings indicates that it is economically feasible to implement a communal cold storage unit if an investor makes the initial investment and allow the fishermen to have a pay-back period of at least one year. Another finding is that the capacity of the mini-grid may need to increase to be able to cover the demand during the periods of low production of the solar PVs, where investments in increase capacity in solar PV and battery. The causal loop diagram indicates that access to electricity can be an important solution to reduce the spoilage by enabling the use of cold storage. In conclusion, access to electricity is important to small scale fisheries in rural areas, and it can help them to increase their income and decrease food insecurity.
Keywords: solar PV mini-grids; spoilage in fishery; cold storage; Africa; Tanzania